Edukasi dan Pendampingan Kontrak Bisnis Syariah bagi Pengusaha Mikro di Era Digital - Eko Mulyadi; Ribut Suwarsono; Farida; Faida Martigo Wati; Tiara Depita (Vonis, 2025)
This study aims to analyze the effectiveness of an educational and mentoring program on Sharia business contracts for micro-entrepreneurs in enhancing Islamic economic law literacy and improving their adaptability to digital contracts in the era of economic transformation. The program was motivated by the limited understanding of Sharia contract principles among micro-entrepreneurs and the weak legal aspects in drafting business agreements. The implementation method consisted of three stages: participants’ needs analysis, conceptual education on Sharia contract law, and practical mentoring in drafting and applying digital Sharia-based contracts. Evaluation was conducted through pre-tests and post-tests, contract portfolio analysis, and participatory observation. The results indicate a significant improvement in participants’ understanding, from 54% to 96%, and a 65% increase in their ability to draft Sharia business contracts. Furthermore, 80% of participants successfully produced electronic contract drafts using murabahah and musyarakah schemes consistent with Sharia principles and the provisions of Law No. 11 of 2008 on Electronic Information and Transactions (ITE Law). These findings demonstrate that an educational and participatory approach effectively fosters legal awareness, business ethics, and technological readiness among micro-entrepreneurs. Conceptually, the program strengthens the integration between Sharia values and business digitalization, establishing a foundation for a just, transparent, and sustainable micro-enterprise ecosystem.